Phase-resolved X-ray polarimetry of the Crab pulsar with the AstroSat CZT Imager. (January 2018) - Vadawale, S.; Chattopadhyay, T.; Mithun, N.; Rao, A.; Bhattacharya, D.; Vibhute, A.; Bhalerao, V.; Dewangan, G.; Misra, R.; Paul, B.; Basu, A.; Joshi, B.; et al.
Abstract The Crab pulsar is a typical example of a young, rapidly spinning, strongly magnetized neutron star that generates broadband electromagnetic radiation by accelerating charged particles to near light speeds in its magnetosphere1 . Details of this emission process so far remain poorly understood. Measurement of polarization in X-rays, particularly as a function of pulse phase, is thought to be a key element necessary to unravel the mystery of pulsar radiation2–4 . Such measurements are extremely difficult, however: to date, Crab is the only pulsar to have been detected in polarized X-rays5–8 and the measurements have not been sensitive enough to adequately reveal the variation of polarization characteristics across the pulse7 . Here, we present the most sensitive measurement to date of polarized hard X-ray emission from the Crab pulsar and nebula in the 100–380 keV band, using the Cadmium–Zinc–Telluride Imager9 instrument on-board the Indian astronomy satellite AstroSat10 . We confirm with high significance the earlier indication6, 7 of a strongly polarized off-pulse emission. However, we also find a variation in polarization properties within the off-pulse region. In addition, our data hint at a swing of the polarization angle across the pulse peaks. This behaviour cannot be fully explained by the existing theoretical models of high-energy emission from pulsars. Sensitive X-ray polarization measurements of the Crab pulsar by the Indian AstroSat satellite confirm earlier indications of strongly polarized off-pulse emission but also reveal variations in polarization properties within the off-pulse region.